Assessment of green growth in the Baltic States - Dalia Štreimikienė (Contemporary Economics, 2024)
EU Green Deal and US Green New Deal strategies indicate that green growth is at the center of the policy agendas of many developed countries and regions. The green growth is a key element in achieving sustain- able development. Green growth is an economic growth strategy that prioritizes human development while guaranteeing that natural resources continue to provide environmental services to the current and future generations to achieve their sustainable development. There are many definitions of green growth, and many indicators and measures have been developed to assess green growth results for countries. The paper aims to analyze green growth indicators and measures and develop a case for a comparative assessment of green growth achievements in the Baltic States. The Baltic States were ranked based on their achievements accord- ing to specific dimensions of green growth, and policy recommendations to promote green growth were developed based on conducted research.
Keywords: P18; Q01; Q32; Q58; 330; green growth; indicators; assessment; ranking; Baltic States